1984
DOI: 10.3758/bf03199972
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral CRs elicited by a lithium- or an amphetamine-paired contextual test chamber

Abstract: The behavioral CRs elicited by a drug-paired contextual cue in rats were measured in a series of experiments. The first three experiments measured the pattern of CRs elicited by a lithiumand an amphetamine-paired CS chamber. The final experiment measured the pattern of URs elicited by lithium or amphetamine when administered in the same chamber. The suppression of grooming-related activities (body washing, face washing, and/or scratching) appeared as a nonspecific effect of both drug USs that was capable of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 13 publications
1
41
1
Order By: Relevance
“…This finding is inconsistent with previous research showing that LiCl administration causes a suppression of both horizontal and vertical activity (e.g. Johnson, 1975;Smith, 1981;Parker et al, 1984;Tenk et al, 2005). Specifically, the dose of LiCl used in the current study, 64 mg/kg, has been shown to produce significant decreases in the number of gridline crossings, rearing frequency, and time to reach the wall of an open-field (Smith, 1983).…”
Section: Unconditioned Effects Of Liclcontrasting
confidence: 82%
See 1 more Smart Citation
“…This finding is inconsistent with previous research showing that LiCl administration causes a suppression of both horizontal and vertical activity (e.g. Johnson, 1975;Smith, 1981;Parker et al, 1984;Tenk et al, 2005). Specifically, the dose of LiCl used in the current study, 64 mg/kg, has been shown to produce significant decreases in the number of gridline crossings, rearing frequency, and time to reach the wall of an open-field (Smith, 1983).…”
Section: Unconditioned Effects Of Liclcontrasting
confidence: 82%
“…This delay between injections was intended to overlap the peak of behavioural effects of the two drugs during the conditioning trial. LiCl exerts maximum effects on behaviour 15-30 min following drug administration (e.g., Parker et al, 1984) while acute CORT has effects within 7-15 min following injection (e.g., Sandi et al, 1996a). The first injection was either 64 mg/kg LiCl or NaCl (10 ml/kg) and the second was either 5.0 mg/kg CORT or vehicle; depending on group assignment.…”
Section: Conditioningmentioning
confidence: 99%
“…Finally, the results of the present experiments add to the growing body of evidence showing that exposure to a distinctive context followed by an injection of LiCl establishes a context-LiCl association in rats. Previously this association has been revealed by reexposing rats to the distinctive context and observing their behavior (e.g., Meachum & Bernstein, 1992;Parker et al, 1984) or by studying the ability of this learning to block subsequent flavor-illness learning in that context (e.g., Best, Brown, & Sowell, 1984;Krane, 1980;Rudy, Iwens, & Best, 1977;Symonds & Hall, 1997;Westbrook & Brookes, 1988;Willner, 1978). The present experiments show that this learning also reliably alters pain sensitivity in rats.…”
Section: Discussionmentioning
confidence: 60%
“…By contrast, exposure to a context previously paired with an injection of LiCl provokes a suppression of grooming and exploratory behaviors as well as the emergence of freezing (e.g., Meachum & Bernstein, 1992;Parker, Hills, & Jensen, 1984). It is unknown whether this exposure also regulates pain sensitivity in rats.…”
mentioning
confidence: 93%
“…Two observers scored behavior for 20 min and recorded latency to the LOB response. LOB was characterized by periods of immobility, lack of grooming, and a flattened, stretched out posture (Parker et al 1984;Meachum and Bernstein 1990). Mice not observed in the LOB position at any time during the testing period received a latency score of 20 min.…”
Section: Licl Toxicitymentioning
confidence: 99%